ANALYSIS OF A MICRO-SCALE URBAN PLANNING-BASED SIGNAGE SYSTEM AS A MEDIUM FOR ENVIRONMENTAL EDUCATION AND SAFETY IN THE HIGH-DENSITY RESIDENTIAL AREA OF KRICAK URBAN VILLAGE, YOGYAKARTA - Wajar Bimantoro; Bambang Pilu Hartato; Raden Arditya Mutwara Lokita (SOSIOEDUKASI, 2026)
This study examines the need for a signage system based on micro-scale urban planning as an edu-safety medium in the high-density residential area of Kricak Urban Village, Yogyakarta City. High-density settlements have complex spatial characteristics, including narrow alleys, intersections, community activity nodes, public facilities, and environmentally vulnerable areas that require clear visual information. This study employed a descriptive qualitative approach through field observation, interviews, and visual documentation. The findings show that the existing signage system has not yet been integrated as a visual system for the area, as it still varies in form, color, font size, material, and placement. The required signage system includes orientation signs, directional signs, facility identification signs, environmental regulation signs, cleanliness education signs, evacuation routes, “Titik Kumpul” signs, and warnings for vulnerable areas. An effective signage system design needs to consider legibility, visual consistency, information hierarchy, installation points, and local identity. Therefore, the signage system can support spatial legibility, community education, and improved environmental safety preparedness in high-density residential areas in a more directed, communicative, functional, and sustainable manner.